Dukungan Suami Dengan Proses Adaptasi Psikologi Pada Ibu Nifas RSAD Denpasar Bali - Ariani, Ni Komang Sri; Darmayanti, Putu Ayu Ratna; Santhi, Wulan Tertiana (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
The postpartum period is the period after giving birth which is prone to postpartum depression. Psychologically, a woman who has just given birth often experiences mental distress, because the mother's emotions become unstable, sad, and easily offended. The husband's support is the most influential factor in adjusting the mother's emotional state. The study was to determine the relationship between the husband's support and the psychological adaptation process of postpartum mothers at the Denpasar Hospital in Bali. This research is an analytic observational study with a cross-sectional approach, a sampling method with total sampling within the number of samples is 50 people. The results showed that most of the postpartum mothers who receive good husband support (N=22; 38.8%) experienced a safe and smooth taking-in phase (N=14; 13.6%). Postpartum mothers who received less husband support (N=9; 20%) experienced a phase of taking in postpartum blues in as many as 3 people. There was a significant relationship between the husband's support and the psychological adaptation process of postpartum mothers at RSAD Denpasar (p0.001). Husband's support is very influential in maintaining the psychological stability of postpartum mothers and good husband's support can prevent postpartum blues.